The Upregulation of Molecules Related to Tumor Immune Escape in Human Pituitary Adenomas - Xi, Zhiyu; Jones, Pamela S.; Mikamoto, Masaaki; Jiang, Xiaobin; Faje, Alexander T.; Nie, Chuansheng; Labelle, Kathryn E.; Zhou, Yunli; Miller, Karen K.; Soberman, Roy J.; Zhang, Xun (Frontiers in Endocrinology, 2021)
Human pituitary adenomas are one of the most common intracranial neoplasms. Although most of these tumors are benign and can be treated medically or by transphenoidal surgery, a subset of these tumors are fast-growing, aggressive, recur, and remain a therapeutic dilemma. Because antibodies against immune checkpoint receptors PD-1 and CLTA-4 are now routinely used for cancer treatment, we quantified the expression of mRNA coding for PD-1, CLTA-4, and their ligands, PD-L1, PD-L2, CD80, and CD86 in human pituitary adenomas and normal pituitary glands, with the ultimate goal of exploiting immune checkpoint therapy in aggressive pituitary adenomas. Aggressive pituitary adenomas demonstrated an increased expression of PD-L2, CD80, and CD86 in compared to that of normal human pituitary glands. Furthermore, aggressive pituitary tumors demonstrated significantly higher levels of CD80 and CD86 compared to non-aggressive tumors. Our results establish a rationale for studying a potential role for immune checkpoint inhibition therapy in the treatment of pituitary adenomas.